ANALYSIS OF THE ROLE OF SUSTAINABLE TOURISM VILLAGE CERTIFICATION IN EFFORTS TO PROTECT TOURISM VILLAGE MANAGEMENT REVIEWED FROM LAW NO 10 OF 2009 ON TOURISM (CASE STUDY : PENGLIPURAN VILLAGE, BALI) - Gratia Wirata Laksmi; Hulman Panjaitan; Hendri Jayadi Pandiangan; Diana R.W Napitupulu (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Sustainable tourism village certification is one of the sustainable tourism certification products issued by the Indonesian Sustainable Tourism Certification Council. The sustainable tourism village certification program was initiated by the Ministry of Tourism and Creative Economy in 2020 aimed at developing sustainable tourism in Indonesia. Penglipuran Tourism Village has community-based and sustainable tourism management, but the management's human resources need to be strengthened. Meanwhile, sustainable management requires specific knowledge and skills to reduce the negative impacts of tourism. The aim of this research is to analyze efforts to protect the management of Tourism Villages through sustainable tourism village certification based on Law of the Republic of Indonesia no. 10 of 2009 on Tourism. This research is normative legal research with a statutory approach, analysis of legal concepts (analytical conceptual approach), and case study methods supported by secondary data. Researchers found that the role of sustainable tourism village certification as a condition for business standardization in the form of business certification was studied in the form of preventive and repressive legal protection means. Preventive legal protection is regulated in Article 19 and Article 52 of Law No. 10 of 2009 on Tourism. Repressive legal protection is regulated in Articles 27, 62, 63 and 64 of Law No. 10 of 2009 on Tourism.